High density continuous production of murine pluripotent cells in an acoustic perfused bioreactor at different oxygen concentrations. Issue 2 (18th September 2012) - Baptista, Ricardo P.; Fluri, David A.; Zandstra, Peter W.
Abstract: Strategies for the production of pluripotent stem cells (PSCs) rely on serially dissociated adherent or aggregate‐based culture, consequently limiting robust scale‐up of cell production, on‐line control and optimization of culture conditions. We recently developed a method that enables continuous (non‐serially dissociated) suspension culture‐mediated reprogramming to pluripotency. Herein, we use this method to demonstrate the scalable production of PSCs and early derivatives using acoustic filter technology to enable continuous oxygen‐controlled perfusion culture. Cell densities of greater than 1 × 10 7 cells/mL were achieved after 7 days of expansion at a specific growth rate ( µ ) of 0.61 ± 0.1 day −1 with a perfusion rate ( D ) of 5.0 day −1 . A twofold increase in maximum cell density (to greater than 2.5 × 10 7 cells/mL) was achieved when the medium dissolved oxygen was reduced (5% DO). Cell densities and viabilities >80% were maintained for extended production periods during which maintenance of pluripotency was confirmed by stable expression of pluripotency factors (SSEA‐1 and Nanog), as well as the capacity to differentiate into all three germ layers. This work establishes a versatile biotechnological platform for the production of pluripotent cells and derivatives in an integrated, scalable and intensified stirred suspension culture. Biotechnol. Bioeng. 2013; 110: 648–655. © 2012 Wiley Periodicals, Inc. Abstract : Strategies for the production of pluripotent stem cells (PSCs) rely on serially dissociated cultures limiting robust scale‐up of cell production, on‐line control and optimization of culture conditions. Baptista, Fluri, and Zandstra demonstrate the scalable production of PSCs and early derivatives using acoustic filter technology to enable continuous oxygen‐controlled perfusion culture. This work establishes a versatile biotechnological platform for the production of pluripotent cells and derivatives in an integrated, scalable, and intensified stirred suspension culture.